Impact of Women's Representation in Corporate Governance on Financial Performance of Sharia Banks in Indonesia - Via Muthmainnah Luthfi; Muhamad Umar Mai; Ruhadi Ruhadi (Jurnal Riset Akuntansi dan Keuangan, 2024)
The study aims to analyze the impact of women's representation in corporate governance on the Islamic Commercial Banks performance in Indonesia during the period 2010-2022. The independent variables in this research include the women’s board of commissioners (BCWMN), women’s board of directors (BDWMN), women’s sharia supervisory board (SSBWMN), and women’s audit committee (ACWMN), with dependent variables being ROA and ROE. Data analysis employs panel data regression with the fixed effect Generalized Least Squares (GLS) model implemented through Stata version 17. The research findings indicate that BCWMN and BDWMN do not influence ROA but have a positive effect on ROE. Conversely, ACWMN negatively impacts both ROE and ROA, while their SSBWMN does not affect either ROE or ROA.